Technology proximity between firms and universities and technology transfer - Martin Woerter (ETH Zurich, KOF Swiss Economic Institute, 2009)
This paper investigates the technological orientation of firms and universities and their propensity to have knowledge and technology transfer (KTT) activities. This study looks at the technological potential for KTT and how it is used, emphasizing differences between smaller and larger firms. To this end we collected information about the technology activities of firms (patent statistics) and the technology activities of universities. Furthermore we used survey data on technology transfer activities. We combined the three datasets and found - especially for smaller firms - that great technology proximity fosters transfer activities with different universities (case 1). The same is true, if proximity is low and expertise is considerable at universities in the respective technology field (case 2). In both cases additional transfer potential exists. In the second case firms engage in transfer activities in order to update and modifying their knowledge base and as a consequence improve competitiveness in certain technology fields. Furthermore firms show a tendency to diversify their contacts with universities in order to avoid knowledge lock-in.
Keywords: 330; Innovation; Knowledge and Technology Transfer; Technology Proximity; Universities; Firms; Innovation; Technologietransfer; Forschungskooperation; Produktdifferenzierung; Schweiz